(untitled) (Research, Society and Development, 2020)
The present work addresses suicide, an evil practice that has been affecting the whole world. In the face of alarming data, it was decided to investigate in reality in Picos - PI the behavioral profile of suicidal cases. This is a documentary, retrospective, descriptive cross-sectional research with a quantitative approach, conducted through a survey of secondary sources dating suicide cases and suicide attempts from January 2013 to December 2018. At the end it is concluded that the suicide attempts were much higher than the suicide suicide cases. Among the years studied, 2017 was the one with the most occurrences, with a peak of cases in May. Thus, this article aims to analyze the behavioral profile of suicidal cases that occurred in Picos-Piauí, in the period from 2013 to 2018.